2007
DOI: 10.1063/1.2772273
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational structure, spin-orbit splitting, and bond dissociation energy of Cl2+(X̃Πg2) studied by zero kinetic energy photoelectron spectroscopy and ion-pair formation imaging method

Abstract: The isotopomer-resolved vibrational and spin-orbit energy structures of Cl(2) (+)(X (2)Pi(g)) have been studied by one-photon zero kinetic energy photoelectron spectroscopy. The spin-orbit energy splitting for the ground vibrational state is determined as 717.7+/-1.5 cm(-1), which greatly improves on the accuracy of the previously reported data. This value is found to be in good agreement with the ab initio quantum chemical calculation taking account of the inner shell electron correlation. The first adiabatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 32 publications
(59 reference statements)
2
34
0
Order By: Relevance
“…The CASPT2 sum energy value of -1.30 eV for Cl 2 (X 1 R g -) ? O 2 (X 3 R g -) is in good agreement with the experimental sum energy values of -1.31 eV [43]. The previously reported CAS-CI sum energy value (0.76 eV) [27].…”
Section: O-o and O-cl Dissociation Potential Energy Curves From Clooclsupporting
confidence: 81%
See 1 more Smart Citation
“…The CASPT2 sum energy value of -1.30 eV for Cl 2 (X 1 R g -) ? O 2 (X 3 R g -) is in good agreement with the experimental sum energy values of -1.31 eV [43]. The previously reported CAS-CI sum energy value (0.76 eV) [27].…”
Section: O-o and O-cl Dissociation Potential Energy Curves From Clooclsupporting
confidence: 81%
“…For example, the sum energy of the reactant group = 2 9 the calculated total energy value of ClO (X 2 P) at its optimized geometry minus the calculated total energy value of ClOOCl (1 1 A) at its optimized geometry. The previously reported experimental [2,7,20,43] and theoretical [25,27] sum energy values (relative to 1 1 A) are listed in Table 3. The CASPT2 sum energy value of 0.70 eV for ClO (X 2 P) ?…”
Section: O-o and O-cl Dissociation Potential Energy Curves From Clooclmentioning
confidence: 99%
“…These studies indicated that a broad range of vibrational levels of the X + and A + states could be studied (σ g ) 2 (π u ) 4 (π * g ) 3 X + 2 g (σ g ) 2 (π u ) 3 (π * g ) 4 A + 2 u (σ g ) 1 (π u ) 4 (π * g ) 4 2 + g (σ g ) 2 (π u ) 4 (π * g ) 2 (σ * u ) 1 4 − u , 2 u , 2 − u , 2 + u at high resolution by pulsed-field-ionization zero-kineticenergy (PFI-ZEKE) photoelectron spectroscopy and that information on the mechanisms leading to ion-pair formation in the photoionization of Cl 2 might be obtained from such studies. PFI-ZEKE photoelectron spectra of the low vibrational levels (v + ≤ 6) of the X + state with partial rotational resolution were reported by Li et al 9 who also determined precise values of the first adiabatic ionization energy of Cl 2 and of the threshold for Cl + ( 1 D 2 ) + Cl − ( 1 S 0 ) ion-pair formation. A recent high-resolution measurement of the threshold ion-pairformation spectrum of Cl 2 19 near the Cl + ( 3 P J , J = 0 − 2) + Cl − ( 1 S 0 ) thresholds led to the observation of ion-pair states of very high principal quantum numbers (≥1800) and to the observation of interactions between series of ion-pair states converging to different ion-pair dissociation thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…9. The band centersν 0v + derived from the analysis of the rotational structure are listed in Tables II and III and formed …”
Section: Rotational Structure Of the Spectramentioning
confidence: 99%
See 1 more Smart Citation